The Worlds around Taiwo Shango - Matzke, Christine (Journal of African Cultural Studies, 2025)
Introduction: This special issue is a first stepping stone towards the recuperation and reappraisal of the long-lost television film Taiwo Shango oder: Der zweite Tag nach dem Tod [Taiwo Shango or: The Second Day after the Death] (1965, dir. Klaus Stephan), a co-production by the Bayerischer Rundfunk (BR, Bavarian Broadcasting) and Westdeutscher Rundfunk Köln (WDR, West German Broadcasting Cologne) in conjunction with the Nigerian Television Service (NTS). It also draws attention to the extensive photographic legacy of Nina Fischer-Stephan (1922–2018), who documented life in Nigeria from the late 1950s to the mid-1960s, and whose work cannot be separated from the production of Taiwo Shango. Contributions emerged out of a joint Nigerian–German research collaboration between the universities of Lagos and Bayreuth (UniLag and UBT, July 2021–December 2022), which initially focused on close readings of the film in relation to contemporaneous and contemporary cultural production and cultural industries in Nigeria and Germany. Also included are the voices of scholars who usually do not study media and performance but share illuminating insights into the contexts of the film; and initial responses to the first outdoor installation of Fischer-Stephan’s pictures in Lagos in 2022. The Stephan and Fischer-Stephan estate is held at Iwalewahaus,University of Bayreuth, Germany, whose first director was Ulli Beier.
Keywords: Taiwo Shango; TV film; Nigerian-German collaboration; Klaus Stephan; Nina Fischer-Stephan; Christopher Kolade; Segun Olusola; Yorùbá history